Steering Committee Draft Major Milestone #8 1977 - Ted Grandsen::::::; Tom Laubacher::::::; Alfred Nunez::::::; Joe Garrett:::::: (1977)
A report detailing various land use alternatives with various different developmental routes based on those alternatives.